Low T-Cell Responses to Mitogen Stimulation Predicts Poor Survival in Recipients of Allogeneic Hematopoietic Stem Cell Transplantation - Yong, Michelle K.; Cameron, Paul U.; Slavin, Monica A.; Cheng, Allen C.; Morrissey, C. Orla; Bergin, Krystal; Spencer, Andrew; Ritchie, David; Lewin, Sharon R. (Frontiers in Immunology, 2017)
Background: Successful engraftment and reconstitution of the innate and adaptive immune system are associated with improved outcomes in recipients of allogeneic hematopoietic stem cell transplantation (HSCT). A clinically meaningful and simple biomarker of immunosuppression could potentially assist clinicians in their decision-making. We aimed to determine the relationship between T-cell production of interferon gamma (IFN-γ) in response to phytohaemagglutinin (PHA) to clinical outcomes in HSCT recipients. Methods: A prospective observational multi-centre study of 73 adult allogeneic HSCT recipients was conducted in Melbourne, Australia. Eligible participants were >18 years and at risk of cytomegalovirus disease. T-cell responses to PHA were assessed at 3, 6, 9 and 12 months post-HSCT using the commercial Quantiferon-CMV assay which quantifies IFN-γ production by ELISA following stimulation with PHA. A low response was defined as IFN-γ<0.5 IU/ml following stimulation with PHA. Results: At 3 months post-HSCT, high responses to PHA (median IFN-γ 7.68 IU/ml) were seen in 63% of participants and low responses to PHA (median IFN-γ 0.06 IU/ml) in 37%. IFN-γ responses to PHA were significantly associated with the severity of acute graft versus host disease (AGVHD) (spearman r=-0.53 p<0.001) and correlated with blood lymphocyte count (spearman r=0.52 p<0.001). Twelve month overall survival was greater in individuals with high compared to low IFN-γ response to PHA at 3 months (92% vs. 62% respectively, Cox proportional hazard ratio (HR): 4.12 95% CI: 1.2-13.7, p=0.02). Non-relapse mortality (NRM) was higher in individuals with low IFN-γ response to PHA (competing risk regression HR 11.6 p=0.02). In individuals with no AGVHD compared to AGVHD and high IFN-γ response to PHA compared to AGVHD and low IFN-γ response to PHA, 12 month survival was 100% vs. 80% vs. 52%, respectively (log rank test p<0.0001). Conclusion Low IFN-γ response to PHA at the 3 month time-point following allogeneic HSCT was predictive of reduced 12 month overall survival, increased NRM and reduced survival in recipients with AGVHD. Assessing IFN-γ response to PHA post HSCT may be a clinically useful immune biomarker.